Avatar: the Last Airbender and philosophy : wisdom from Aang to Zuko - De Cruz, Helen; De Smedt, Johan (Blackwell philosophy and popculture series, 2023)
The world is out of sorts. The four nations, Water, Earth, Fire, and Air, are imbalanced because of the unrelenting conquest of the Fire Nation. The only one who can restore balance to the world is the Avatar. On the face of it, Avatar: The Last Airbender is a story about a lone superhero. However, saving the world is a team effort, embodied in Team Avatar, aka the Gaang. Aang needs help from his friends and tutors, even from non-human animals. Through the teachings of Guru Pathik and Huu he comes to realize that though the world and its nations seem separate, we are all one people. We all have the same roots and we are all branches of the same tree. Avatar: The Last Airbender and Philosophy brings to the fore the Eastern, Western, and Indigenous philosophies that are implicit in the show. Following Uncle Iroh's advice that it is important to draw wisdom from many traditions, this volume features contributions by experts on Buddhist, Daoist, Confucian, and Indigenous schools of thought, next to focusing on Western classical authors such as Plotinus, Kant, and Merleau-Ponty. The volume is also unique in drawing on less common traditions such as black abolitionism, anarchism, and the philosophy of martial arts